Base deficit is a predictor of mortality in organophosphate insecticide poisoning. (February 2018) - Lee, SB; Kang, C; Kim, DH; Kim, T; Lee, SH; Jeong, JH; kim, SC; Rhee, DY; Lim, D
Objective: Organophosphate insecticide (OPI) self-poisoning is a major medical problem in many countries. Several studies have demonstrated that the base deficit (BD) is a prognostic tool that is correlated with the severity of injury and predicted mortality, particularly in trauma patients. Here, we aimed to investigate the prognostic significance of BD in OPI poisoning. Methods: This retrospective observational study was conducted between January 1, 2006, and January 31, 2015, at a single emergency department (ED). The BD values were divided into quartiles according to the number of patients: 3 mEq/L or less, 3–5.9 mEq/L, 6–9.9 mEq/L, and 10 mEq/L or greater. Survival at 30 days from ED admission was estimated using the Kaplan–Meier survival analysis. Results: Among 154 patients, 31 died, yielding a mortality of 20.1%. The highest BD quartile (≥ 10 mEq/L) and the 6–9.9 mEq/L group were associated with an increased risk of 30-day mortality. Patients with a BD of 10 mEq/L or greater had a 5.85-fold higher risk of 30-day mortality and patients with a BD of 6–9.9 mEq/L had a 5.40-fold higher risk of 30-day mortality compared to patients with a BD of 3 mEq/L or less. The area under the curves of the BD and the Acute Physiology and Chronic Health Evaluation II score for mortality were 0.748 (95% confidence interval (CI), 0.660–0.835) and 0.852 (95% CI, 0.789–0.915), respectively. Conclusions: This study showed that the BD is a predictor of 30-day mortality in patients with OPI poisoning.